Analisis Kesantunan Berbahasa Mahasiswa dalam Pesan Whatsapp terhadap Dosen Program Studi Pendidikan Bahasa Indonesia : Kajian Pragmatik - Avida Alfi Atuzzahro; Farida Yufarlina Rosita; Berlian Pancarrani (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
The purpose of this study is to determine the maxims of politeness of language used when communicating with lecturers via WhatsApp. This study uses a qualitative descriptive approach method, data collection techniques, namely interviews and observations, other supporting data, namely screenshots of WhatsApp chats of students and lecturers. And using the word "sorry" to respect the interlocutor, sorry for disturbing his time, or disturbing his comfort, in the maxim of wisdom the speaker shows respect for the interlocutor, the maxim of appreciation shows respect for the opinion of the interlocutor, the maxim of generosity shows responsibility, the maxim of simplicity shows the humility and humility of the speaker, the maxim of agreement shows an agreement between lecturers and students, the maxim of sympathy, shows respect and sympathy for the interlocutor. Violation of politeness maxim of tact Hari senin bisa saya bimbingan ngga bun the speaker does not give a choice. A speaker's consensus maxim is unable to prepare himself in forming an agreement.